Elechek . Elechek - Rakhmadieva, Nailya (Soros Foundation Kyrgysztan, 2006)
Duration: 00:26:00 Sairash was an exemplary wife for twenty years. After her wedding, she put her former life 'on hold' and began to create a new one with her husband, building a house with the modest means available and finding joy in every new success on the road to their future together. When the new home was finally completed, her husband brought a new, younger, wife into the household, deciding to form a family with both the women, and their children. Sairash rebelled, however. She couldn't stand the new order and after a while she left home. In rebelling against the accepted order, did she become a bad wife, or an example and model for all oppressed women? Weaving together scenes from Sairash's daily routine with frank interviews – both with Sairash herself and those close to her – the filmmaker creates a picture of her transformed life. She thus portrays the inner workings of a woman who has found a new meaning in life, but whose happiness will never be complete without a husband and her children. The documentary is also a commentary on the current post–war situation in Kyrgyzstan where the number of women exceeds that of men, thus leading to frequent cases of polygamy. Sairash, rebelling against the strong, but unfair, order, still wears the elechek – the traditional high headdress worn by elderly married women in Kyrgyzstan. The filmmaker sensitively contrasts her rebellion with the conservative majority view that families should stay together, no matter what the cost.